Quantum Efficiency Enhancement of Bialkali Photocathodes by an Atomically Thin Layer on Substrates. Issue 23 (16th October 2019) - Yamaguchi, Hisato; Liu, Fangze; DeFazio, Jeffrey; Gaowei, Mengjia; Guo, Lei; Alexander, Anna; Yoon, Seong In; Hyun, Chohee; Critchley, Matthew; Sinsheimer, John; Pavlenko, Vitaly; Strom, Derek; et al.
Abstract : Quantum efficiency (QE) enhancement in accelerator technology relevant to antimonide photocathodes (K2 CsSb) is achieved by interfacing them with atomically thin 2D crystal layers. The enhancement occurs in a reflection mode, when a 2D crystal is placed in between the photocathodes and optically reflective substrates. Specifically, the peak QE at 405 nm (3.1 eV) increases by a relative 10%, whereas the long wavelength response at 633 nm (2.0 eV) increases by a relative 36% on average and up to 80% at localized "hot spot" regions when photocathodes are deposited onto graphene‐coated stainless steel. There is a similar effect for photocathodes deposited on hexagonal boron nitride monolayer coatings using nickel substrates. The enhancement does not occur when reflective substrates are replaced with optically transparent sapphire. Optical transmission, X‐ray diffraction (XRD), and X‐ray fluorescence (XRF) revealed that thickness, crystal orientation, quality, and elemental stoichiometry of photocathodes do not appreciably change due to 2D crystal coatings. These results suggest that optical interactions are responsible for the QE enhancements when 2D crystal sublayers are present on reflective substrates, and provide a pathway toward a simple method of QE enhancement in semiconductor photocathodes by an atomically thin 2D crystal on substrates. Abstract : Quantum efficiency (QE) enhancement in accelerator technology relevant to antimonide photocathodes (K2 CsSb) is achieved by interfacing them with atomically thin 2D crystal layers. The enhancement occurs in a reflection mode, when a 2D crystal is placed in between the photocathodes and optically reflective substrates.